Evaluation of Greywater as a Sustainable Source of Irrigation for Ornamental Crops in Green Walls—A Study of Plant and Soil Using Ruellia tuberosa - Shaheeda Marakkar Anangadan (19239607) (2024)
Green walls and roofs are sustainable building systems with several benefits. However, the irrigation requirements of these building systems conflict with water sustainability goals in water-scarce places. This study investigates using greywater directly to irrigate ornamental species for such situations by examining the effects of freshwater and greywater irrigation on Ruellia tuberosa growth, plant health and soil characteristics. Five replicates for each condition were grown for 91 days. Greywater irrigation led to a 15% higher plant growth height, a 31% higher plant biomass (p = 0.065), and a 71% increase in stem biomass (p < 0.001) compared to freshwater irrigation. However, greywater-irrigated plants had reduced chlorophyll content (10.7%, p < 0.001), and increased leaf chlorosis (p = 0.003), likely caused by stress from laundry and detergent chemicals. Greywater irrigation led to greater mineral content in greywater-irrigated plant biomass and soil for all minerals tested, most notably boron, which was deficient in the soil. Greywater-irrigated soil also had a higher organic content according to FTIR and electron dispersive spectroscopy. Greywater irrigation improved nutritional and soil conditions, including phosphate, which helped Ruellia tuberosa flourish. This study suggests raw greywater can replace freshwater in water-scarce climates for green wall irrigation instead of high-energy onsite greywater treatment systems. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su16031183